Penguatan Budaya Keselamatan Dan Implementasi Keselamatan di Tempat Kerja - Fuadi, Yan; Marlina, Marlina; cahyono, Bagyo; iwan (EUNOIA, 2022)
Behavior based safety is an effective method for preventing work accidents, this method is widely applied in European countries and the United States. Behavior based safety can achieve the target of the occupational safety index and can also provide a structural approach to safety management in the long term. The main purpose of the occupational safety and health program is to avoid or at least minimize the occurrence of work accidents. In order for the construction implementation process to run smoothly and well, it is necessary to pay attention to the factors of occupational safety and health for all parties involved in the project. The method used in the delivery of service materials is a workshop (question and answer). Occupational Health and Safety (K3) has an effect on Work Productivity. So with the increase in occupational safety and health of employees, it will be able to increase work productivity